MENINGKATKAN KEMAMPUAN ANAK AUTIS DALAM MENGENAL JENIS-JENIS PEKERJAAN MELALUI MEDIA POWER POINT (Penelitian tindakan Kelas di SLB Autis Harapan Bunda Padang) - Nurleni - Nurleni (Universitas Negeri Padang, 2012)
This research aim to the 1) Description of execution of study improve to recognize work types by using power point of medium at autis of child SLB Autis Harapan Bunda Padang. 2) Please prove that media of power point can imporove ability recognize work type by using power point medium autis of child in SLB Autis Harapan Bunda Padang. This research by using method classroom action research collaboration with coleage. Data collected by observatin and tes technique, later than analysed qualitative and quantitative. Result of research indicate that 1) study process recognize work type with two cycle. Cycle one seven times meeting which early with activity of planning, final activity and execution. Cycle two the four of times. 2) Result of study recognize work type with power point of medium tes early value “A” (10) while “I” still (0). Cycle I assess ability recognize type work of child mount namely: both child (A dan I) obtaining 70. While cycle II increase to mount “A” obtaining (100) and “I” obtaining (90) from five tested work type. Thereby, can be concluded taht media of power point can improve ability recognize w ork type to autis of child class D.III SLB Autis Harapan Bunda Padang.